Simultaneous Carcinomas of the Breast and Ovary: Utility of Pax-8, WT-1, and GATA3 for Distinguishing Independent Primary Tumors from Metastases. (May 2015) - Espinosa, Inigo; Gallardo, Alberto; D'Angelo, Emanuela; Mozos, Ana; Lerma, Enrique; Prat, Jaime
Abstract : Breast carcinomas rarely metastasize to the ovary and are even more rarely present clinically as primary ovarian tumors. However, patients with breast cancer not infrequently develop independent primary ovarian carcinomas. In these cases, distinction between independent primaries and metastatic tumors is crucial. Several comparative immunohistochemical studies have been reported, but few included significant clinicopathologic data and none investigated cases of ovarian and breast carcinomas from the same patients. In this study, we compared 18 cases of patients with bona fide independent breast and ovarian carcinomas (15 high-grade serous and 3 clear cell carcinomas), with 9 cases of patients with known mammary carcinomas (7 lobular and 2 ductal carcinomas) metastatic to the ovary. Immunohistochemical stains for Pax-8, WT-1, and GATA3 were carried out on tissue microarrays (TMA). Most primary ovarian carcinomas were larger than the metastatic tumors ( P =0.001) and were diagnosed at an advanced stage. All primary ovarian tumors showed marked nuclear pleomorphism, whereas only 2 metastatic breast carcinomas had Grade 3 nuclei ( P =0.000). The vast majority of ovarian metastases (7/9) showed the typical pattern of lobular breast carcinoma. Pax-8 and WT-1 expression were found in 16 of 18 (88%) and 13 of 18 (72%) primary ovarian carcinomas, respectively. In contrast, all primary ovarian carcinomas were negative for GATA3. The 2 Pax-8-negative ovarian carcinomas were also negative for WT-1. With the exception of 3 triple-negative carcinomas, all primary breast carcinomas were positive for GATA3. All metastatic breast carcinomas were positive for GATA3 and negative for Pax-8. WT-1 expression was seen in only 1 of 9 metastatic breast carcinomas (11%). Patients with ovarian metastases had worse prognosis than patients with independent breast and ovarian carcinomas ( P =0.000). Pax-8, WT-1, and GATA3 immunoreactions are useful in the distinction between independent primaries and metastatic mammary carcinomas to the ovary in the light of clinicopathologic findings.